EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK DISKUSI TERHADAP KEPERCAYAAN DIRI SISWA SMPN 24 KOTA JAMBI - Khofifah, Khairani; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of self-confidence of some students of SMPN 24 Kota Jambi which is shown through hesitant behavior in expressing opinions, nervousness when performing in front of the class, and tend to be passive in group activities. This study aims to determine the effectiveness of group guidance services with discussion techniques in increasing the self-confidence of students of SMPN 24 Kota Jambi. The study used a quantitative approach with a pre-experimental experimental method and a one group pretest-posttest design. The research sample consisted of 8 grade VIII students selected using a purposive sampling technique based on the recommendation of the guidance and counseling teacher. The research instrument was a self-confidence questionnaire consisting of 26 valid items with a Cronbach's Alpha reliability of 0.839. Data were analyzed using the Shapiro-Wilk normality test and paired samples t-test with the help of SPSS 27. The results showed that the average score of students' self-confidence increased from 66.12 in the pre-test to 114.25 in the post-test. The results of the paired t-test showed a significance value of 0.001 <0.05, so the alternative hypothesis was accepted. Thus, group guidance services using discussion techniques have proven effective in increasing the self-confidence of students at SMPN 24, Jambi City.